2017
DOI: 10.1007/s10354-017-0592-0
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal microbiome-gut-brain axis and irritable bowel syndrome

Abstract: SummaryPsychological comorbidity is highly present in irritable bowel syndrome (IBS). Recent research points to a role of intestinal microbiota in visceral hypersensitivity, anxiety, and depression. Increased disease reactivity to psychological stress has been described too. A few clinical studies have attempted to identify features of dysbiosis in IBS. While animal studies revealed strong associations between stress and gut microbiota, studies in humans are rare. This review covers the most important studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
52
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(57 citation statements)
references
References 63 publications
0
52
0
5
Order By: Relevance
“…A connection between the faecal microbiota’s composition and function and psychological disorders seems to be established, but it is poorly understood [ 7 , 9 ]. The connection is not explained by one or a few species or genus [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A connection between the faecal microbiota’s composition and function and psychological disorders seems to be established, but it is poorly understood [ 7 , 9 ]. The connection is not explained by one or a few species or genus [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…The gut-brain axis is a bidirectional link between the gut and the brain and of importance for various psychobiological disorders, such as anxiety, depression, fatigue, stress reactions, pain syndromes, and functional gastrointestinal disorders [ 7 , 8 , 9 ]. The absolute or relative amounts of the gut microbes per se and the microbes’ metabolic products are possible mediators of the gut-brain effects.…”
Section: Introductionmentioning
confidence: 99%
“…At intestinal level, an increasing number of studies characterizing the intestinal gut microbiota have shown that perturbations of gut microbiota are associated with the development of different diseases, such as colorectal cancer [ 7 , 8 ], Crohn’s disease [ 9 ], irritable bowel syndrome (IBS) [ 10 ], neurological [ 11 ] or renal diseases [ 12 ] and, in most cases, a loss of intestinal epithelial barrier function-produced by pro-inflammatory compounds such as the bacterial lipopolysaccharide LPS has been identified [ 2 , 10 , 12 ]. At the nasal epithelium, results of in vitro studies suggest that epithelial tight junctions may be affected by protease activities of pollen and house dust mite allergens in allergic rhinitis, leading to an abnormally permeable epithelium with alterations in the tight junctions (changes in expression and localization of tight junction proteins) [ 3 , 5 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Patients are stratified into four subtypes based on the predominant bowel habit: constipation-predominant IBS (IBS-C), diarrhea-predominant IBS (IBS-D), mixed IBS (IBS-M) and unclassified IBS (IBS-U) [1]. Although the precise etiology of IBS remains unknown, the possible mechanisms include visceral hypersensitivity, gut motility dysfunction, immunomodulation disturbances, gut microbiota alterations and an imbalance in brain-gut axis interactions [7][8][9][10]. In addition, new microbiological symptoms following acute infectious gastroenteritis might also suggest a microbiological pathogenesis for IBS [11].…”
Section: Introductionmentioning
confidence: 99%